Prevention of Air Embolism in Extracorporeal Membrane Oxygenation Systems: An In Vitro Study on Protection of Central Venous Catheter Lumen - Danilo Franco; Nejc Krasna; Robert Novak; Giovanni Esposito; Raffaele Izzo; Jan Belohlavek; Marko Noc; Tomaz Goslar (Medicina)
Background and Objectives: This study aimed to investigate the risk and mechanisms of air entry into the extracorporeal membrane oxygenation (ECMO) circuit through the central venous catheter (CVC) in a veno-venous configuration. The primary goal was to assess the impact of different air volumes on ECMO circuit performance at varying pump speeds. Material and Methods: The study utilized a circuit model to simulate ECMO conditions and evaluate the potential entry points of air, specifically through the unprotected lumen of the CVC. Various interventions, such as the use of a closed three-way stopcock or clave, were implemented to assess their efficacy in preventing air entry. Results: The unprotected lumen of the central venous catheter posed a significant risk for air entry into the ECMO circuit. The introduction of a closed three-way stopcock or clave proved effective in preventing air ingress through the central venous catheter. Auditory cues, such as a distinct hissing sound, served as an early warning sign of air presence in the circuit. The study demonstrated that even small volumes of air, as minimal as 1 mL, could pass through the oxygenator at specific pump speeds, and larger volumes could lead to pump dysfunction. Conclusions: The study identified the unprotected lumen of the central venous catheter as a potential entry point for air into the ECMO circuit. The use of a closed three-way stopcock or one-way valve was found to be a reliable protective measure against air infiltration. Early detection through the observation of a hissing sound in the circuit provided a valuable warning sign. These findings contribute to enhancing the safety and performance of ECMO systems by minimizing the risk of air embolism.